Socio-Economic Correlation of Scavenger Community in Religious Life - Delta Aria Rudi; T Safir Iskandar Wijaya; T. Murdani (Winaya Inspirasi Nusantara Foundation, 2021)
The problem in this research is about how the impact of the socio-economic life of the scavenger community on religious life, and what are the obstacles that exist in the scavenger community in religious life. to answer the above questions, the author uses a qualitative research method with a field approach method. The research location is Gampong Jawa Landfill, Kutaraja Subdistrict, Banda Aceh City, while the data sources come from direct observation, in-depth interviews with (twelve) selected respondents from all groups of waste pickers in Gampong Jawa Landfill as well as additional documentation data or archives of the waste pickers. Then the data is processed, analyzed in an easy-to-understand descriptive manner. The results of this study indicate that the socio-economic life of the scavenger community is still vulnerable to poverty, as for the income obtained to meet household needs from scavenging in the landfill has not been able to neutralize the needs of life from the sale of used goods, aqua bottles, cardboard, atoms and so on. Economic inequality in meeting household needs has an impact on religious life, including, scavengers who are on landfill land when the adhan arrives are still preoccupied with collecting used goods, then attending houses that die with the Gampong community is often not well realized. So that the values that blend about worship are not well realized in every scavenger's daily life.